Description of a new species of the leafhopper genus Ulopsina (Hemiptera: Cicadellidae: Ulopinae) from China with a key to species - Wang, Dongming; Zhang, Yalin (Zootaxa, 2019)
The leafhopper genus Ulopsina (Hemiptera: Cicadellidae: Ulopinae) is studied and a new species, Ulopsina bimaculata, from China is described and illustrated. A species checklist and a key to all known species of Ulopsina from China are provided.